A day in the life of a paediatric surgeon: a PAPSA research study. Issue 2 (April 2016) - Bradshaw, Catherine J.; Lakhoo, Kokila
Abstract : Objectives: This study aimed to create a snapshot picture of the global workload of paediatric surgeons and identify differences between countries. Methods: Surgeons from 13 paediatric surgical units in different countries across the world were asked to record the number and type of admissions to the paediatric surgery service over a 24-h period from 8 a.m. on 23 May 2012. Results: Data were recorded for 13 units from 13 countries: 11 low and middle income countries (LMICs) and two high-income countries (HICs). Dar es Salaam, Tanzania, had the greatest number of admissions. Two units in HICs had the lowest number of admissions, other than the Nigerian unit, which only had three admissions due to a hospital strike on the day surveyed. The percentage of emergency admissions ranged from 38 to 83%. Those units with the highest number of total admissions tended to also have the highest proportion of emergencies. Trauma was the most frequently reported admission reason, accounting for 18% of admissions. However, there were no cases of trauma in HIC units. Conclusion: The spectrum of paediatric surgery differs between countries, in particular between LMICs and HICs. Units in LMICs tend to have a greater number of admissions, including a wider variety of conditions and a higher proportion of emergency work. Paediatric surgery in LMICs faces many challenges. This highlights the importance of training specialist paediatric surgeons in these countries. Further data are still needed to fully outline the burden of disease in paediatric surgery, especially in LMICs.